2012
DOI: 10.4253/wjge.v4.i8.356
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of extent of early gastric cancer using flexible spectral imaging color enhancement

Abstract: The demarcation line between the cancerous lesion and the surrounding area could be easily recognized with flexible spectral imaging color enhancement (FICE) system compared with conventional white light images. The characteristic finding of depressed-type early gastric cancer (EGC) in most cases was revealed as reddish lesions distinct from the surrounding yellowish noncancerous area without magnification. Conventional endoscopic images provide little information regarding depressed lesions located in the tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…However, it is often difficult to detect gastric superficial adenocarcinomas using conventional endoscopy with white-light imaging (C-WLI). Many clinical studies have reported on the diagnostic performance of EGC by imageenhanced endoscopy (IEE) techniques such as narrow-band imaging (NBI) [2][3][4][5][6][7][8][9] or flexible spectral imaging color enhancement (FICE) [10][11][12]. In particular, magnifying endoscopy with NBI (M-NBI) is a powerful optical IEE that has demonstrated accurate real-time diagnostic performance in EGC compared with C-WLI [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often difficult to detect gastric superficial adenocarcinomas using conventional endoscopy with white-light imaging (C-WLI). Many clinical studies have reported on the diagnostic performance of EGC by imageenhanced endoscopy (IEE) techniques such as narrow-band imaging (NBI) [2][3][4][5][6][7][8][9] or flexible spectral imaging color enhancement (FICE) [10][11][12]. In particular, magnifying endoscopy with NBI (M-NBI) is a powerful optical IEE that has demonstrated accurate real-time diagnostic performance in EGC compared with C-WLI [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often difficult to diagnose superficial EGC using C-WLI. Image-enhanced endoscopy techniques such as narrow-band imaging (NBI) [1], autofluorescence imaging [2], flexible spectral imaging color enhancement [3,4,5], and i-scan [6] have found wide applications for endoscopic diagnosis of EGC. In particular, magnifying NBI (M-NBI) is reportedly superior to C-WLI for the accurate diagnosis of EGC [7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However recent advances with this procedure have been made, and a new endoscope (model EG-580NW, Fuji Film, Co.) were manufactured beginning in October 2011. This endoscope is a trans-nasal model that provides high-quality endoscopic images with a wide field view of (140°) and is equipped with the flexible spectreal imaging color enhancement (FICE) system, which is based on a spectral estimation technique by which the narrow bandwidth is obtained from white light images without optical filters [13][14]. Unfortunately, the FICE system cannot image distinctive microvessels on the tumor surface as sharply as NBI.…”
Section: Discussionmentioning
confidence: 99%
“…The outer diameter of the endoscope is 5.9 mm. This endoscope is a trans-nasal model that provides high-quality endoscopic images with a wide field view (of 140°), and is equipped with the flexible spectral imaging color enhancement (FICE) system, which enhances images by extracting spectral images at the desired wavelengths via the application of signal processing to the white light generally used by endoscopes [13][14]. However, given the limited ability of conventional white light illumination to achieve high-cotrast imaging of microvessels in the mucosal surface layer, a more effective system was needed.…”
Section: Equipmentmentioning
confidence: 99%